The prevalence of sleep disorders in adults with learning disabilities: A systematic review. - Shanahan, Paul; Ahmad, Shahnaz; Smith, Kimberley; Palod, Swapnil; Fife‐Schaw, Chris (British Journal of Learning Disabilities, 2023)
Background: Previous research indicated a high prevalence of disordered sleep among adults with learning disabilities, however issues with design impacted findings. The current systematic review aims to: (a) present how disordered sleep and sleep disorders amongst adults with learning disabilities are described in the literature, and (b) report on the prevalence of disordered sleep and sleep disorders among adults with learning disabilities. Methods: Five databases (EMBASE, MEDLINE, PsycARTICLES, PsycINFO and PubMed) were searched for articles published from 1900 to October 2021 that examined the prevalence of disordered sleep and/or sleep disorders in adults aged 18 or older with learning disabilities. The Joanna Briggs Institute critical appraisal checklist for prevalence studies was used to assess study quality and prevalence is described and reported as ranges. The study was registered on PROSPERO (ID: CRD42019134550). Findings: A total of 27 studies were selected. Twenty studies (n = 8043 participants) examined the prevalence of disordered sleep and identified prevalence ranging from 6.1% to 74.2% across a range of sleep parameters. Twelve studies examined sleep‐related breathing disorders (n = 2558 participants) and identified prevalence which ranged from 0.5% to 100%. There was notable heterogeneity between studies in terms of quality, definition of disordered sleep, measurement of sleep, and study design. Conclusion: There was a variable prevalence of disordered sleep among people living with learning disabilities. There were problems in meaningfully synthesising results due to heterogeneity in measurement, diagnosis, study design and study quality. Based on these limitations, we suggest that future studies should seek to utilise objective, replicable and consistent measures of sleep in this population and control for physical health factors which could influence prevalence such as epilepsy and iatrogenic effects. Accessible summary: Good studies have found that more than 1 in 13 people with learning disabilities find it hard to sleep, for example find it difficult to fall asleep at night.Over 1 in 3 people with certain types of learning disability have breathing difficulties during sleep. We need to find out how much this is affecting their life.Better ways to measure sleep should be used when doing future research and helping people who find it hard to sleep. For example, using activity watches.